Alternative Strategy to Analyze In Vitro Cell Invasion of 3D Cultures - Rodrigues Fernandes, Natalie Ap [UNESP]; Rodrigues Nascimento, Camyla [UNESP]; González Maldonado, Laura Andrea; Rossa Junior, Carlos (MyJove, 2024)
Spheroid culture is a 3D model that provides an improved replication of the in vivo microenvironment compared to traditional two-dimensional (2D) cultures. Invasion is a cellular outcome of utmost interest in cancer biology. In this protocol, we have devised an alternative strategy for evaluating cancer cell invasion in vitro, employing heterospheroids comprised of oral squamous cell carcinoma (OSCC), cancer-associated fibroblasts (CAF), and monocytes. These heterospheroids aim to mimic the tumor microenvironment (TME), including two relevant non-neoplastic cell types alongside the cancer cells. Each cell type was labeled with vital fluorescent markers emitting in distinct wavelengths before spheroid formation. Once formed, heterospheroids were seeded onto a layer of human leiomyoma-derived extracellular matrix in the upper compartment of a microporous membrane. Invasion was assessed in the z-axis using confocal microscopy. Digital images were obtained in the corresponding fluorescent channels at 10 µm intervals, covering a depth of 90 µm in the z-axis. Analysis was performed using freeware image software by calculating the integrated fluorescence intensity in each image and fluorescence channel. This approach enables a more dynamic analysis of cell invasion patterns in a multilayered context, as well as the examination of spatial co-localization of different cell types during invasion.